Exploring the application of Corynebacterium glutamicum single cell protein in the diet of flathead grey mullet (Mugil cephalus): effects on growth performance, digestive enzymes activity and gut microbiota - Bertini, Andrea; Natale, Silvia; Gisbert, Enric; Andrée, Karl B.; Concu, Danilo; Dondi, Francesco; De Cesare, Alessandra; Indio, Valentina; Gatta, Pier Paolo; Bonaldo, Alessio; Parma, Luca (Frontiers in Marine Science, 2023)
The capacity of utilising a single cell protein (SCP) ingredient coming from Corynebacterium glutamicum was assessed on adult grey mullet (Mugil cephalus) reared in captive conditions. The experiment was carried out using triplicate groups of grey mullet of 68 g average initial body weight. Three diets, SCP0, SCP10 and SCP20 with increasing inclusion of SCP (0%, 10% and 20%) in substitution of soybean, poultry and fish meal were formulated to contain 30% protein, 10% fat and 18.5 Mj/kg feed of digestible energy. After 113 days, fish fed SCP diets presented significantly lower growth performance and a significant lower activity of the alkaline proteases and aminopeptidases compared to fish fed diet without SCP inclusion. Gut microbiota appeared modulated by SCP inclusion being dominated at the phylum level by Fusobacteria in fish fed SCP0 (51.1%), while in fish fed SCP10 (67.3%) and SCP20 (53.2%) Proteobacteria was dominant. Data evinces a deficiency in the protein utilisation as a cause of the poor growth performance in fish fed the SCP diets. A hypothesis has been proposed that an incomplete SCP cell-wall lysis accounts for this outcome because of the particular organisation of the digestive system of grey mullet (which lack of an acidic stomach digestion) and the failing in the development of a functional gizzard (no access to sand in captive conditions). Even though the outcomes of this research were quite unexpected, they will improve our knowledge on the digestive system of flathead grey mullet and provide some theoretical basis for an improved development of low FM and SBM aquafeed for the species.